Institutional cross-ownership of peer firms and investment sensitivity to stock price - CHO, Young Jun (Institutional Knowledge at Singapore Management University, 2022)
Theory suggests that stock price guides managers in corporate decisions as managers learn from price. We reason that cross-ownership lowers information processing costs and increases industry specialization, improving revelatory price efficiency (Bond, Edmans, and Goldstein 2012). Consistent with our expectations, we find that a firm’s investment-q sensitivity increases as its cross-ownership increases, suggesting that cross-ownership facilitates managerial learning from price and thus investment efficiency. We strengthen the causal inference by conducting a difference-in-differences analysis using financial institution mergers as an identification strategy. We also find that the increase in the investment-q sensitivity associated with cross-ownership is more pronounced for firms with a lower propensity of voluntary disclosure, for firms with managers of less private information, and for firms with higher stock liquidity. Overall, these results suggest that cross-ownership can induce more efficient corporate decisions by helping investors better produce private information and transmit it to stock price.